AB0344 A Retrospective Non-Interventional Study on The Use of Biologics in The Treatment of Australian Patients with Rheumatoid Arthritis-The Real Study. (15th July 2016) - Nicholls, D.; Griffiths, H.; Barrett, R.; Button, P.; Truman, M.; Bird, P.; Roberts, L.; Tymms, K.; Littlejohn, G.
Abstract : Background: Medication choices offered to rheumatoid arthritis (RA) patients are based in part on results from randomised controlled trials (RCTs). While these trials form a valuable evidence-base for rational prescribing, extrapolation of RCTs data to every day clinical practice is hampered by the highly selected patient (pt) groups that are accepted into RCTs. The comparative effectiveness of biologic treatment regimens in a real world Australian population is unknown. Objectives: To assess effectiveness of biologic (b) DMARDs, as monotherapy, in combination with conventional (c) DMARDs other than MTX and in combination with cDMARDs regimens including MTX in the Australian OPAL database. Methods: A retrospective non-interventional study. Data was extracted from participating Australian rheumatology centres using point of care software. Pts ≥18 years (yrs) with probable/definite RA, who had been prescribed a bDMARD and have had a visit recorded 12 months prior to and at least 12–40 weeks (wks) after commencement of a bDMARD were included. Bouts of treatment (BTs) refer to cycles of continuous, individual biologics prescribing in individual pts; if pts change biologics then this was defined as a new BT. Wk12 (-4/+8) analyses included any measurement between wk8 and wk20 post bDMARDs initiation and wk24 (-4/+8) included any measurements between wk20 and wk32. Results: 2971 pts met criteria; median age 60 yrs (min 19, max 94) and median disease duration prior to 1st bDMARD of 6.1 yrs (min 0.2, max 58.3). Median number of bDMARDs per pt was 1 (min 1, max 8). At least 1 bDMARD was taken by 2971 pts, 1177 received 2 bDMARDs and 507 received 3 or more. There were 4923 bDMARD BTs recorded for this population with median treatment duration of 0.7 yrs (min 0, max 11.8). Median duration of 1st bDMARD (n=2971 pts)=0.8 yrs (min 0, max 11.8); 2nd bDMARD (n=1177)=0.6 yrs (min 0, max 9.9) and 3rd bDMARD (n=507)=0.6 yrs (min 0, max 6.4). The most commonly used bDMARDs were etanercept (n=1358), adalimumab (n=1098), abatacept (n=642) and tocilizumab (n=629); median duration of BTs=0.7 (min 0, max 11.8), 0.8 (min 0, max 10.5), 0.7 (min 0, max 6.1) and 1.0 (min 0, max 7.4) yrs respectively. bDMARD monotherapy (no cDMARD overlap) was administered in 10% BTs (n=488); bDMARDs + MTX +/− other cDMARD(s) were administered in 74% BTs (n=3639) and bDMARDs + cDMARD(s) other than MTX were administered in 16% BTs (n=796). Median CDAI and DAS28 by biologic presented in Table 1 . Conclusions: The majority in this cohort of Australian RA pts receive 1 line of bDMARD. Pts tend to persist longer on 1st bDMARD than subsequent biologics. bDMARDs as monotherapy or in combination (+/− MTX) are valid treatment strategies in the real world. Acknowledgement: The study was sponsored by Roche Products Pty. Limited. Medical writing was provided by Dr Joseline Ojaimi from Roche. Disclosure of Interest: D. Nicholls: None declared, H. Griffiths: None declared, R. Barrett Employee of: Roche Products, Pty. Limited, P. Button Employee of: Roche Products, Pty. Limited, M. Truman Employee of: Roche Products, Pty. Limited, P. Bird: None declared, L. Roberts: None declared, K. Tymms: None declared, G. Littlejohn: None declared